Clinical utility of viscoelastic testing (TEG and ROTEM analyzers) in the management of old and new therapies for hemophilia. Issue 2 (7th December 2018) - Ramiz, Sarah; Hartmann, Jan; Young, Guy; Escobar, Miguel A.; Chitlur, Meera
Abstract: Hemophilia A and B are rare inherited bleeding disorders resulting from deficiency of coagulation factors VIII and IX respectively. In the past few decades, the field of hemophilia has witnessed pivotal management challenges and therapeutic advances. Routine coagulation and factor assays, while useful in the classification of severity and treatment monitoring in hemophilia patients, have been shown to be of limited use in managing clinical presentations and outcomes. This prompted the investigation of viscoelastic studies in hemophilia care, which have established their utility in various bleeding and thrombotic states. In this review, we will discuss and critically assess the current literature highlighting the use of viscoelastic studies in various aspects of hemophilia including the determination of clinical phenotype, management of patients with inhibitors, perioperative management, and monitoring of novel agents.